The Place Marketing Concept of Rural Towns in Northern Sweden: What is the Unique Selling Point? - Olga Kompaniets; Daniel Rauhut (European Regional Science Association (ERSA), 2013)
The place marketing concept is one of the popular concepts to analyze and promote countries, regions, cities and towns. The intensification of competition for investment, tourism and human resources among European cities and towns has increased the importance of being unique. Consequently this has opened up the field for specialists in marketing and branding in terms of geographic, social, economic, political, cultural and historical and ethno-cultural development. Most of studies on place marketing however focus on the unique selling points and brands of countries, the capitals and the big cities, while rural towns need more marketing attention due to overcoming the lack of material and non-material resources in the towns. This is based on the idea of promotion to target markets of unique selling point of the town. These rural towns have lots to offer â?? unfortunately nobody have heard about them and the towns do not know what to promote! The aim of this paper is to discuss to what extent the place marketing concept as a necessary condition for an effective promotion of 80 rural towns in the seven northernmost regions in Sweden. Towns with more than 50,000 inhabitants have been excluded from the analysis. The paper presents reasons for using the place marketing concept by rural towns in Northern Sweden. Also it contains features of the place marketing concept and its key elements for rural towns, describes the target audience for rural towns with their specific needs and wants. This is of outmost importance to these municipalities where a majority of them struggle with declining populations. The theoretical framework of this paper consists of marketing theory, the theory of place marketing, place branding and place development. The empirical material is based upon statistics on local economic development and population trends as well as information about the towns provided on their homepages. A qualitative research method, theory building, and comprehensive integrated approach to practices of place marketing for rural towns is used in this paper. The study is giving recommendations for rural townsâ?? government how to find its unique selling point and to start use the key elements of place marketing concept in more effective and systematic way.
Keywords: M31; Z13; R58; 330; place marketing; rural towns; target audience; unique selling point